survay of Mothers\' Behavior and Perceptions of Benefits and barriers in Preparing healthy breakfast and snacks for school children - Sakineh Rakhshanderou; Mohtasham Ghaffari; ameneh pooresmaeildorosteh (Iranian Association of Health Education and Health Promotion, 2020)
Background and Objective: Healthy breakfast and snacks have important role to student thought and body health. The aim of this study was to survey the Behavior And perceptions of mothers about the benefits and barriers of preparation of healthy breakfast and snacks for school children. Materials and Methods: Descriptive-analytical study was conducted in 2017. 315 elementary school boys and girls selected by cluster random sampling and their mothers were invited to participate in the study. Data were collected using by questionnaires that included demographic characteristics, questions related perceived benefits, perceived barriers and behavior. Questionnaires Validity were assessed in two ways face and content validity. Test-retest method and internal consistency were used for questionnaires reliability. Data were collected and analyzed by SPSS 16 software and using T-tests and ANOVA.    Results: The significant difference between the perceived benefits of mothers and their employment status (p<0.001) but no significant relationship between mothers' perceived interests with other demographic variables (P>0.05). There was a significant difference between mothers' behavior with age (P-value <0.041) and spouse's education (P-value<0.000) and the most crucial perceived barriers among mothers for preparing healthy breakfast and snacks were hurry, not having enough income and time, breakfast as a boring (P<0.001). Conclusion: According to the results of the study, it is better to planning and designing educational interventions to solve children's nutritional problems should be done to reduce perceived barriers of mothers.